2014
DOI: 10.1308/003588414x13946184902523
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of postoperative urinary retention in patients undergoing elective hip and knee arthroplasty

Abstract: INTRODUCTION Postoperative urinary retention requiring urethral catheterisation increases the risk of joint sepsis following arthroplasty. Spinal anaesthesia with opiate administration is used widely in lower limb arthroplasty. We sought to establish whether the choice of opiate agent had any effect on the incidence of postoperative retention and therefore the risk of joint sepsis. METHODS A total of 445 consecutive patients who underwent primary elective lower limb arthroplasty were reviewed retrospectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 20 publications
0
38
1
Order By: Relevance
“…Literature extensively discusses Post-operative urinary retention as a common complication of opioid regional anesthesia [10]. Urinary retention with epidural/intrathecal delivery of buprenorphine is also a known effect on the lower urinary tract [11].…”
Section: Discussionmentioning
confidence: 99%
“…Literature extensively discusses Post-operative urinary retention as a common complication of opioid regional anesthesia [10]. Urinary retention with epidural/intrathecal delivery of buprenorphine is also a known effect on the lower urinary tract [11].…”
Section: Discussionmentioning
confidence: 99%
“…18 There is more evidence that routine urethral catheterization is not needed in patients who have spinal anesthesia without opioids. 19,20 However, a recent multicenter study of patients undergoing fast-track total joint arthroplasty reported a 40% rate of urinary retention. 9 In addition, male sex and a history of benign prostatic hypertrophy are associated with an increased risk of retention.…”
Section: History Of Nocturia May Guide Urinary Catheterization For Tomentioning
confidence: 99%
“…1 Postoperative urinary retention can lead to significant morbidity, such as prosthetic infection and sepsis. 2 The spread of infection from the urinary tract to cause deep joint sepsis has been well documented and is more common following knee arthroplasty with a quoted incidence of 2.5% as compared with 0.64% post-hip arthroplasty. 1 Studies have shown increased incidence of urinary retention in patients using epidural when compared with nonepidural techniques.…”
Section: Introductionmentioning
confidence: 99%